Regulation of Illegal Drugs: State Control and Fragile Institutional Capacity. Issue 3 (29th November 2019) - Snapp, Zara; Tinasti, Khalid; Herrera Valderrábano, Jorge
This policy comment analyzes the risks and issues that might arise from the legal regulation of illegal narcotic and psychotropic products or substances with risks to the health or safety of citizens. We focus on reducing these risks by providing existing examples through existing state-based control mechanisms, with a focus on developing economies with fragile or corruption-sensitive institutions. We discuss the need to implement regulatory models that minimize the risk of diversion and corruption from the legal to the illegal market within a regulated framework. The primary concern is to establish legal and regulatory frameworks and policies with sufficient resilience to mitigate and reduce the risks, and that are inclusive of broad regulation stakeholders and the influence of their interactions on regulation outcomes. Importantly, we look at the integration of current players of the illegal market into the legal one in order to enhance the social, economic and legal benefits of regulation towards the most vulnerable, while at the same time undermining the illegal market. We find that state institutions, including those of LMICs, have varying institutional capacity to regulate currently prohibited drugs, with the existence of regulation frameworks of legal drugs or hazardous and controlled goods. While the technical health and judiciary mechanisms exist to allow for more effective controls of drugs through legal regulation, political will is still lacking. We reviewed regulation models using a social justice focus, thereby allowing countries to establish frameworks for the inclusion of the populations most-affected by prohibition and depriving criminal organizations of local networks of trafficking.